2014
DOI: 10.1021/mp500483v
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV as a Potential Target for Selective Prodrug Activation and Chemotherapeutic Action in Cancers

Abstract: The efficacy of chemotherapeutic drugs is often offset by severe side effects attributable to poor selectivity and toxicity to normal cells. Recently, the enzyme dipeptidyl peptidase IV (DPPIV) was considered as a potential target for the delivery of chemotherapeutic drugs. The purpose of this study was to investigate the feasibility of targeting chemotherapeutic drugs to DPPIV as a strategy to enhance their specificity. The expression profile of DPPIV was obtained for seven cancer cell lines using DNA microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In addition, dipeptidyl peptidases 1–3 and tripeptidyl peptidase 2, which all may bear a potential as prodrug bioconverting enzymes, were identified from the mouse brain and not in plasma. At least, dipeptidyl peptidase 4 (DPP4, EC 3.4.14.5) has been studied as a selective prodrug-activating enzyme in cancer cells ( Dahan et al, 2014 ). However, the possibility of all the above-mentioned enzymes being the main bioconverting enzyme of the studied prodrugs was ruled out by the fact that this enzyme was cobalt-dependent and activated in elevated pH (8.5), which is optimal only for aminopeptidase B from the listed enzymes in Figure 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dipeptidyl peptidases 1–3 and tripeptidyl peptidase 2, which all may bear a potential as prodrug bioconverting enzymes, were identified from the mouse brain and not in plasma. At least, dipeptidyl peptidase 4 (DPP4, EC 3.4.14.5) has been studied as a selective prodrug-activating enzyme in cancer cells ( Dahan et al, 2014 ). However, the possibility of all the above-mentioned enzymes being the main bioconverting enzyme of the studied prodrugs was ruled out by the fact that this enzyme was cobalt-dependent and activated in elevated pH (8.5), which is optimal only for aminopeptidase B from the listed enzymes in Figure 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides of being a famous therapeutic target for the treatment of type 2 diabetes, DPP-IV also exhibits costimulatory role in T-cell activation, adhesion to extracellular matrix proteins, and serves as the functional receptor for Middle East respiratory syndrome coronavirus infection (Ohnuma et al, 2008;Raj et al, 2013). Recently, DPP-IV has come back into the centre of attention as a novel molecular marker or a potential therapeutic target for cancer (Cordero et al, 2009;Javidroozi et al, 2012;Dahan et al, 2014;Arrebola et al, 2014;Davies et al, 2015). Furthermore, increasing evidence has demonstrated that the abnormal presence or altered level of DPP-IV in plasma can serve as a potential biomarker for early diagnosis and prognosis evaluation of many diseases, including cholestasis, non-alcoholic fatty liver disease and lung diseases (Perner et al, 1999;Firneisz et al, 2010;Sánchez-Otero et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Their inhibitors have been introduced to clinics as a class of oral hypoglycemic drugs (called gliptins) that are commonly used to treat type 2 diabetes mellitus and have been demonstrated to efficiently enhance endogenous insulin secretion . DPP IV has previously been associated with the start and progression of several human cancer types; hence, it is considered an important molecular marker and therapeutic target for cancer. , DPP IV is overexpressed in human renal carcinoma tissues, and its blockage reduced several cancer-related processes in the human renal carcinoma cell line Caki-2 . DPP IV has also been shown to be overexpressed in several human colon cancer tissues and in the human Caco-2 colorectal cancer cell line. , In cancerous prostate, the DPP IV activity was enlarged 2-fold versus benign prostatic hyperplasia.…”
mentioning
confidence: 99%
“… 20 DPP IV has previously been associated with the start and progression of several human cancer types; hence, it is considered an important molecular marker and therapeutic target for cancer. 21 , 22 DPP IV is overexpressed in human renal carcinoma tissues, and its blockage reduced several cancer-related processes in the human renal carcinoma cell line Caki-2. 23 DPP IV has also been shown to be overexpressed in several human colon cancer tissues and in the human Caco-2 colorectal cancer cell line.…”
mentioning
confidence: 99%